پلانسازی شاری کوردی له سه ده کانی ناوه راستدا - خضر, پ.ی د. ئاراس اسماعیل; حاجى, پ.ی د. زریان; غریب, م.علی هجران محمد (Sulaimani Journal for Humanities, 2023)
This article deals with the importance of the city because it is one of the most important element of civilization. The city and its social, economic, intellectual, administrative, and political developments represent the vital intensity and the effective part of the movement of civilized progress for any society. The Mesopotamian civilization is one of the most important civilizations in this region. The result of this research concludes that the current cities are influenced by Mesopotamia and its following civilizations, such as the Islamic civilization. This article mainly focuses on a Kurdish city, despite the fact that it has its own history but has recently been counted as an Islamic city.
Keywords: urban planning in Mesopotamian civilization Kurdish City Kurdish city planning